SISTEM MONITORING SUHU DAN INTENSITAS CAHAYA PADA SOLAR PANEL 3 WP BERBASIS IoT (INTERNET OF THINGS) - Alfith, Alfith; Premadi, Aswir; Bachtiar, Antonov; Al Habib, Sayyid (Jurnal Teknologi dan Vokasi, 2023)
According to the solar insolation map, Indonesia has a daily intensity of solar radiation of 4.8 kW/m per day. The potential of solar radiation is highly exploitable and is the most promising source of energy in the future, the energy generated by the sun is unlimited compared to the increasingly depleting fossil energy sources. Many energy experts are already competing to find new discoveries about environmentally friendly alternative energy sources, one of which is solar cells, although efficiency today still requires further consideration. In this study, the authors used the Wemos module with the ESP 8266 type that can be integrated with the Wi-Fi system as its controller, as well as using a temperature sensor with the DHT11 type to detect the temperature in the room and use the LDR sensor as a light intensity detector or as a lux which can be monitored remotely using an internet connection. Light intensity and temperature monitoring results are obtained with light intensity values and temperature values using the application of the highest value = 1005 lux, the lowest value is = 435 lux. For the highest value of the temperature of = 320 Celsius, for the lowest of = 240 Celsius, in sunlight conditions at peak, the resulting value is the light intensity of 1005 lux and the temperature value of 32 ° Celsius which indicates that the weather conditions are very hot.